More than a ’Jágir’: Representation of Transformative Ethos in English Teachers’ Solicited Reflections - Kafle, Hem Raj (Journal of Transformative Praxis, 2021)
This article is based on a generative reading of six English teachers’ solicited responses to reflective questions framed by undergraduate students of science, engineering, and management in Kathmandu University. The reading unfolds four aspects of ethos in the participants – spontaneity, specialties, specialization, and stability –and six frames of reference corresponding with the transformative journey of each participant – teaching is living, made for teaching, making things happen, empowering female students, performing the ideal image and positioned in the opposition. The paper further infers three general traits of the participants as transformed teachers: first, the personality that transcends grumbling and regretting for trivial lacunae involved in the field of teaching; second, the portrayal of a positive picture of teaching as a gifted field; and third, empathy for the students and emphasis on their responsibility of bringing positive changes in students’ lives and in the society at large.